Prostaglandin associated periorbitopathy in patients using bimatoprost, latanoprost and travoprost. (4th August 2013) - Kucukevcilioglu, Murat; Bayer, Atilla; Uysal, Yusuf; Altinsoy, Halil I
Abstract Background To investigate the frequency of prostaglandin‐associated periorbitopathy among bimatoprost, latanoprost and travoprost users. Design Retrospective observational case series. Participants The study group included 105 patients who were using one of the drugs in one eye for more than 1 month, and the other eye was used as a control. Main Outcome Measures The frequency of prostaglandin‐associated periorbitopathy. Methods Special care was taken to detect five prostaglandin‐associated periorbitopathy findings. Hertel exophthalmometry measurements and colour pictures of the periocular area were taken. Results Statistically significant differences were found among the groups regarding the presence of all prostaglandin‐associated periorbitopathy findings (P < 0.05). Periorbital fat loss was the most frequent and was observed in nearly all prostaglandin‐associated periorbitopathy patients except those who were relatively young. The overall frequency of prostaglandin‐associated periorbito pathy was 93.3% in the bimatoprost group, 41.4% in the latanoprost group and 70% in the travoprost group. The frequency of deepening of the upper lid sulcus was 80% in the bimatoprost group, 15.7% in the latanoprost group and 45% in the travoprost group. The frequency of milder changes (the presence of either only periorbital fat loss or dermatochalasis involution or the presence of both) was higher in the latanoprost group (62%) than in the travoprost (35.7%) and bimatoprost (7.1%) groups. Conclusions Prostaglandin‐associated periorbitopathy is as common as other adverse effects when careful examinations are performed and is more frequent and more severe in bimatoprost users. The loss of the periorbital fat pad is the first sign to occur during the evolution of prostaglandin‐associated periorbitopathy, especially in older patients.